Electronic cigarettes : market entry in Iceland? - Hinrik Hinriksson 1990- (2015)
Given that e-cigarettes will reach the required research and manufacturing standard, Artasan, an over-the-counter pharmaceutical company, are evaluating their potential distribution on the Icelandic market. Smoking consumption among Icelanders is of decreasing concern as daily cigarette use has reduced from 33% to only 11.6% in the last 26 years. However, sales of nicotine replacement therapies have evidently been increasing alongside the decreasing use of cigarettes. Globally, e-cigarette interest is growing rapidly although countries differ in regards to their regulation. In addition, e-cigarettes are highly controversial as they have been perceived as potential harm reduction tools for experienced smokers yet also as an immensely concerning item that may lead to the renormalization of smoking. More concerning is that e-cigarettes are promoted with features appealing to youth or non-smokers. An e-cigarette marketing experiment was conducted based on e-cigarettes attributes (relative advantage vs. compatibility) of innovation. A sample of 592 smokers and 224 former smokers participated. Smokers viewed an online advertisement promoting e-cigarettes in which one of three comparison types (two innovation attributes compared to a third control group) were emphasized. Smokers then indicated their interest in trying e-cigarettes and their perceived advantage over NRTs. Demographic variables such as gender and age were also included in the analysis. Results demonstrated the first evidence of e-cigarette use in Iceland where e-cigarettes seem to be more prevalent among either current or former smokers than five out of six nicotine replacement therapies available in Iceland. Further findings indicated no difference between attributes of innovation in regards to smokers’ interest in trying e-cigarettes. However, female smokers were found to be more interested in trying e-cigarettes compared to males. Interest in trying e-cigarettes was also higher among younger participants than older ones. Finally, the perceived ...